Earnings Trend and Performance Relative to Benchmarks: How Consistency Influences Their Joint Use - KOONCE, LISA; LIPE, MARLYS GASCHO (Journal of Accounting Research, 2010)
ABSTRACT Archival research shows that the market reacts to earnings trend as well as to earnings performance relative to analysts' forecasts (i.e., benchmark performance). We conduct four experiments to investigate how and why investors react to these two measures when both are available over multiple time periods. Our results show that investors rely on an earnings measure only when it is consistent over time. When both measures are consistent over time, investors use them in an additive fashion, suggesting that they view them as providing different information about the firm. Further tests show that investors believe that earnings trend and benchmark performance both provide information about a firm's future prospects and management's credibility. Although judged future prospects fully explain the effect of earnings trend on investor judgments, neither judged future prospects nor management credibility completely explains the effect of benchmark performance. Our study has implications for firm managers and researchers.